(untitled) (Academicia Globe: Inderscience Research, 2022)
The article reveals the role of adaptive physical culture for a person. The purpose of this discipline is the development of the physical abilities of a person with deviations in the state of health, due to the functioning of the motor characteristics released by nature and spiritual forces, for maximum self-realization in public life.